Startup de aplicação móvel iservice – uma plataforma de divulgação e prestação de serviços multigênero - MIRANDA, Ewertom Mozart Moraes de (2020)
The objective of this work is to discuss the construction of a mobile application for the dissemination and contracting of services, with the aim of solving problems and proposing improvements in the interaction between providers and consumers - problems that, under the author's eye, have not yet been solved with the tools currently available for the branch. In order to do so, we tried to mature the idea with the opinion of third parties through a field research. And to ensure the construction of the software project with quality, the development of the tool started from the specification of requirements, progressing to analysis and design of systems, until the implementation and testing of the ferment.